On The Determinants of Foreign Direct Investment to Africa: Are There Differences between Conflict and Non-Conflict Countries? - Boachie-Mensah, L. (University Of Ghana, 2017)
Global flows of Foreign Direct Investment (FDI) have seen a boom in the last two decades. This is evident in the annual United Nations’ Conference on Trade and Development (UNCTAD) investment reports. Notwithstanding this, Africa remains the least recipient of global FDI and its share continues to decline. Africa’s predicament has been explained variously. One reason is that Africa is considered unsafe for foreign investments. Proponents of this conjecture base their arguments on the fact that there are widespread incidences of violent conflicts and civil wars in Africa. We, however, believe that the main shortcoming of this explanation stems from failure to recognize the fact that there are countries in Africa that can be said to be “safe”. We take the argument further by examining the heterogeneity of countries based on whether the country has been in conflict. We defined a conflict country to be a country that has recorded at least 1000 battle related deaths in any one given year between 1996 and 2010. We examined variables that are universal in the literature for the two sub-samples and the full sample. Consequently, our objective was to establish whether there is reason for investors to regard countries differently or all countries were the same. We achieved our objective using a panel of 46 countries in Sub-Saharan Africa; 13 of these were classified as conflict and 33 as non-conflict countries. The fixed effects (FE) method was employed in analysing the data because the Hausman test favoured it. Our data showed that conflict countries received more FDI on average than non-conflict countries. Another argument is that foreign investors who come to Africa have been interested in natural resources. The data showed that conflict countries also had more natural resources on average but the regression results showed an inverse and significant relationship with FDI. This relationship is positive for non-conflict countries suggesting that investors who are interested in natural resources prefer non-conflict countries. Overall, our regression results showed that there is indeed a difference in the factors that determined the destination of FDI in Africa. For the full sample, we obtained positive coefficients for natural resources and institutions but these were not statistically significant. Financial development and infrastructure had positive and significant effect on FDI while trade openness and market size had significant but negative relationship with FDI. In the sub-samples, natural resources, institutions, trade openness, infrastructure and financial development had positive and significant coefficients but market size had negative and significant coefficients in all the six models for non-conflict countries. For the conflict sample, there was an adverse impact of natural resources, trade openness and market size on FDI inflows whereas institutions and financial development did not have any significant impact on FDI. What these results suggest is that the factors that attract investors to conflict countries are different from those for non-conflict countries. Consequently, there was heterogeneity among countries in Africa. We confirmed this by conducting a Chow test.
Thesis (MPhil.)
Keywords: Foreign Direct Investment; United Nations’ Conference on Trade and Development (UNCTAD); Violent Conflicts; Civil Wars; Ghana